Marketing social change : changing behavior to promote health, social development, and the environment - Andreasen, Alan R. 1934- (San Francisco : Jossey-Bass, 1995)
Marketing Social Change offers a revolutionary approach to solving a range of social problems - drug use, smoking, pollution, unsafe sex, and overpopulation - by applying marketing techniques and concepts to change behavior. Using illustrative examples of innovative marketing programs, the author describes the process of developing and implementing an effective social marketing strategy. This successful approach is based on Alan R. Andreasen's more than twenty years' experience consulting, teaching, and researching for social marketing programs around the world. This valuable resource offers public health officials, social service agencies, educators, and health care and nonprofit professionals a state-of-the-art approach to marketing social solutions and behavioral change.
Includes bibliographical references and indexes.
Keywords: Social marketing; Social change; Social problems; Behavior modification